Charting a roadmap of the zoo: an institutional approach to corruption-supporting cultural concepts in Poland - Fürstenberg, Alexander; Uhl, Andrzej (Crime, law and social change, 2025)
Culture is indispensable for explaining the persistence of corruption in a country. While studies on historical conditions of corruption can specify broad cultural explanations, they often elude systematic comparison regarding concepts of culture and types of corruption. Therefore, we advance an analytical model to integrate different historical-cultural paths of corruption constructed as social institutions and classified by alignment with inner-group rules and legal norms. Drawing on a literature review, we exemplify our approach along a roadmap of corruption-supporting cultural concepts in Poland. We develop hypotheses about their cultural roots and expected impact on individual and collective forms of corruption today. Our analysis reveals a spectrum of deep-rooted cultural concepts that explain the persistence of corruption in Poland, which can neither be solely linked to foreign influences nor to its communist past.
Gesehen am 20.11.2025